Structural and functional studies of perforin-like proteins implicated in zoonotic parasitic diseases - Williams, S (2019)
MACPF/CDCs are an ancient superfamily of pore forming proteins that have evolved a critical role in both cellular defence and attack. Many copies of MACPF/CDC proteins are released by a cell before binding to target membranes, oligomerising and undergoing a large structural rearrangement to punch a hole into the membrane, typically killing the target cell. In this thesis the steps of pore formation from membrane recognition through to oligomerisation and membrane insertion have been investigated for several recently discovered MACPF/CDC proteins using a combination of structural and computational biology techniques.